Ecological uncivilisation: Precarious world-making after progress. Issue 2 (March 2022) - Savransky, Martin
Responding to the proposition that learning to live in the Anthropocene involves learning how to die, this article problematises the modes of world-making upheld in some of the contemporary proposals for the global reorganisation of societies towards just, socio-ecological transitions beyond the techno-fixes of geoengineering, green growth, and their attendant ideals of progress. Specifically, it critically examines one such proposal that, inspired by process philosophy, has proven deeply influential in China's recent shift in ecological (geo)politics: the idea of an 'ecological civilisation' based on principles of ontological relationality, democratic responsibility, and a new alliance between the sciences and the humanities. The article argues that while such a project rejects the substantive values of modern progress, its regulative notion of civilisation retains the modern story of progress as a mode of valuation and therefore reinscribes imperial, colonial values at the heart of ecology. In response, the article suggests that learning to die in the wake of ecological devastation requires making life outside the modern coordinates of progress, which is to say living without the ideal of civilisation. Seeking to expand the political imagination at a time of socio-ecological transformations, it calls for 'ecological uncivilisation' as a permanent experimentation with improbable forms of world-making and methodologies of life that are envisaged thanks to ongoing histories of decolonisation and not in spite of them; that strive to live and die well but not always better.